Study of ionic liquid as effective additive for minimum quantity lubrication during titanium machining. (August 2015) - Davis, Brian; Schueller, John K.; Huang, Yong
Abstract: The objective of this study is to investigate the effectiveness of ionic liquid (IL), a low melting point salt, as a lubricant additive for minimum quantity lubrication (MQL) implementation during titanium machining. Herein 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6 ), a prototypical IL, has been used as an MQL cutting fluid additive. It is found that IL-based MQL can effectively reduce the tool wear by 60% when compared to dry cutting and 15% more than MQL without BMIM-PF6 . It is also found that IL-based MQL results in the smallest cutting forces, largest saw-tooth/shear band spacing, and best surface finish.